Robotic Collective Memory - Michal Shur-Ofry; Guy Pessach (Washington University Law Review, 2020)
The various ways in which robots and AI will affect our future society are at the center of scholarly attention. This Commentary, conversely, concentrates on their possible impact on humanity’s past, or more accurately, on the ways societies will remember their joint past. We focus on the emerging use of technologies that combine AI, cutting-edge visualization techniques, and social robots, in order to store and communicate recollections of the past in an interactive human-like manner. We explore the use of these technologies by remembrance institutions and their potential impact on collective memory. Taking a close look at the case study of NDT (New Dimensions in Testimony)—a project that uses ‘virtual witnesses’ to convey memories from the Holocaust and other mass atrocities—we highlight the significant value, and the potential vulnerabilities, of this new mode of memory construction. Against this background, we propose a novel concept of memory fiduciaries that can form the basis for a policy framework for robotic collective memory. Drawing on Jack Balkin’s concept of ‘information fiduciaries’ on the one hand, and on studies of collective memory on the other, we explain the nature of and the justifications for memory fiduciaries. We then demonstrate, in broad strokes, the potential implications of this new conceptualization for various questions pertaining to collective memory constructed by AI and robots. By so doing, this Commentary aims to start a conversation on the policies that would allow algorithmic collective memory to fulfill its potential, while minimizing its social costs. On a more general level, it brings to the fore a series of important policy questions pertaining to the intersection of new technologies and intergenerational collective memory.
Keywords: Collective memory; New dimensions in testimony; Artificial intelligence; Collective past; Memory fiduciaries; Robotic collective memory